Radiotherapy-Induced Cardiotoxicity: The Role of Multimodality Cardiovascular Imaging - Podlesnikar, Tomaž; Berlot, Boštjan; Dolenc, Jure; Goričar, Katja; Marinko, Tanja (Frontiers in Cardiovascular Medicine, 2022)
Radiotherapy (RT) is one of the pillars of cancer therapy. High-dose radiation exposure on the thorax is mainly used in the context of adjuvant RT after breast surgery, in lung and esophageal cancer, and as a complement to systemic treatment in lymphoma. Due to the anatomical proximity, the heart inevitably receives some radiation that can result in acute and chronic cardiotoxicity, leading to heart failure, coronary artery disease, pericardial and valvular heart disease. Current evidence suggests there is no safe radiation dose to the heart, which poses a need for early recognition of RT-induced cardiac injury to initiate cardioprotective treatment and prevent further damage. Multimodality cardiac imaging provides a powerful tool to screen for structural and functional abnormalities secondary to RT. Left ventricular ejection fraction, preferably with three-dimensional echocardiography or cardiovascular magnetic resonance (CMR), and global longitudinal strain with speckle-tracking echocardiography are currently the key parameters to detect cardiotoxicity. However, several novel imaging parameters are tested in the ongoing clinical trials. CMR parametric imaging holds much promise as T1, T2 mapping and extracellular volume quantification allow us to monitor edema, inflammation and fibrosis, which are fundamental processes in RT-induced cardiotoxicity. Moreover, associations between serum biomarkers, genetic polymorphisms and cardiovascular risk in patients undergoing chest RT have been demonstrated, providing a platform for an integrative screening approach. The present review summarizes contemporary evidence of RT-induced cardiac injury obtained from multimodality imaging – echocardiography, cardiovascular computed tomography, CMR and nuclear cardiology imaging techniques. Moreover, it identifies gaps in our current knowledge and highlights future perspectives to screen for RT-induced cardiotoxicity.